PENINGKATAN METODE TEKATEKI SILANG (CROSSWORD PUZZLE) DALAM MOTIVASI DAN HASIL BELAJAR POKOK BAHASAN INSTRINSIK DAN EKSTRINSIK SASTRA SISWA KELAS V SD NEGERI 165 PEKANBARU - Usman, Raja (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The purpose of this study is to improve the activities and learning outcomes of Bahasa Indonesia subject matter, and the topic isabout intrinsic and extrinsic elements of prose literature work. The method used is crossword puzzle method for grade V studentsof state elementary school no 165 Pekanbaru. This research is classroom action research (CAR) with guidance from classroomaction research Wardani and Kuswaya Wihardiet (2019). classroom action research was conducted in two cycles. To find outstudents' knowledge, a pre-cycle test is conducted. Then the planning for correction is carried out in cycle I and cycle II. Thesubject of the study was the fifth grade students of state elementary school no 165 Pekanbaru, with the number is 45 students.Data collection method is carried out based on documentation, observation, and tests. Data analysis techniques by analyzingdata through data collection, data presentation, and conclusion drawing. This CAR is carried out in two cycles, each cyclearranges lesson plan, Procedures for implementing, evaluating, reflecting, learning outcomes of Bahasa Indonesian with a totalscore 3230 averaging 70.22; the first cycle is 3353 with an average of 48.89; and cycle II increased to 97.78. For studentscompleteness in pre-cycle is 26.67 cycle I increased to 48.85% and cycle II becomes 97.78%. It can be concluded that the use ofcrossword puzzle method can improve learning outcomes and learning activities of fifth grade students of state elementary schoolno 165 Pekanbaru.